Post-traumatic stress disorder and post-traumatic growth among the adult survivors of the Lushan earthquake: Selecting resilience as the moderator. (March 2018) - Meng, Zhiyi; Wu, Xiumin; Han, Lu
Abstract: On 20 April 2013, a 7.0 magnitude earthquake, the second worst natural disaster after the Wenchuan earthquake in 2008, struck Ya'an, Sichuan, China. This research studies the post-traumatic stress disorder (PTSD) and post-traumatic growth (PTG) among 2001 adult survivors who experienced the 2013 Lushan earthquake. A cross-sectional study was conducted in the severely affected area of Sichuan. A total of 2300 adult residents participated in the random sampling questionnaire survey eight months after the earthquake, and the sample population was 2001. PTSD was found to be negatively correlated with the survivors' PTG and resilience was positively related to PTG, while the negative effects of PTSD on PTG are weakened by the moderating role of resilience. The results indicate that more attention needs to be paid to strengthening the survivors' resilience as this can reduce their PTSD levels and improve their PTG. This study could support psychological relief workers helping survivors who experienced the earthquake and administrators who encounter similar situations in other countries or regions.